Military mediation as an instrument of peaceful settlement of armed conflicts: the role and challenges of using intelligence data - Sliusarenko, Olha (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
Background. In the contemporary security environment – characterized by the rapid proliferation of armed conflicts and hybrid threats – the search for effective tools of peaceful resolution has become increasingly relevant. Military mediation with intelligence support represents a new direction in mediation practice that combines analytical, diplomatic, and operational methods aimed at reducing the escalation potential of conflicts. Its application enhances trust between conflicting parties, facilitates the early detection of ceasefire violations, and creates conditions for sustainable peace.Methods. The study employs an interdisciplinary approach that integrates methods of system analysis, comparative examination of international experience, content analysis of official documents and reports of international organizations, as well as operational modeling techniques. The research analyzes the practice of military mediation in conflicts of different types (Darfur, South Sudan, Ukraine), identifies institutional prerequisites for integrating intelligence structures into negotiation processes, and conducts a qualitative analysis of the normative and ethical aspects of using intelligence data in mediation procedures.Results. The findings demonstrate that military mediation supported by intelligence contributes to the effectiveness of negotiations by reducing information asymmetry, enabling prompt response to escalation risks, and strengthening mutual trust between parties. International practice (UN, African Union, EU) confirms that incorporating verified intelligence data increases the legitimacy of mediators and facilitates informed decision-making on ceasefire arrangements, compliance monitoring, and humanitarian coordination. At the same time, new risks have been identified, associated with the use of artificial intelligence and digital technologies in mediation processes.Conclusions. Military Mediation with Intelligence Support constitutes a promising instrument of contemporary security diplomacy, integrating technological and humanitarian-legal approaches to conflict resolution. Its effectiveness depends on the quality of intelligence data, the transparency of information-sharing procedures, and compliance with international legal standards. Future research should focus on developing operational models for integrating intelligence data into negotiation process, thereby strengthening peace sustainability and mitigating emerging forms of violence.
Keywords: military mediation, intelligence support, negotiation process, armed conflict, international law, ethical standards, information asymmetry, peaceful conflict resolution, analytical intelligence, international security